The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2019
DOI: 10.1111/jjns.12283
|View full text |Cite
|
Sign up to set email alerts
|

Effect of parenting stress, self‐esteem and parent–child interaction in parents of children with allergic rhinitis on self‐esteem of children: Analysis of Actor‐partner Interdependence Model

Abstract: Aim It is important to focus on the early identification of factors that promote children's self‐esteem, to foster the healthy development of children with allergic rhinitis. This study aimed to identify the effects of parents' parenting stress, self‐esteem, and parent–child interaction on the self‐esteem of children with allergic rhinitis. Methods Structural equation modeling was used to verify the conceptual model. This study was conducted on 656 children with symptoms of allergic rhinitis and their parents … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
2
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 31 publications
0
2
0
Order By: Relevance
“…Second, parenting stress influenced self-esteem, which affected the life satisfaction of both parents. These results are similar to the findings of a Korean study conducted on 656 children diagnosed with allergic rhinitis and their parents, which found that fathers' parenting stress influenced mothers' self-esteem [32]. Furthermore, these results support the findings that positively evaluating oneself is linked to one's QOL [33].…”
Section: Discussionsupporting
confidence: 89%
“…Second, parenting stress influenced self-esteem, which affected the life satisfaction of both parents. These results are similar to the findings of a Korean study conducted on 656 children diagnosed with allergic rhinitis and their parents, which found that fathers' parenting stress influenced mothers' self-esteem [32]. Furthermore, these results support the findings that positively evaluating oneself is linked to one's QOL [33].…”
Section: Discussionsupporting
confidence: 89%
“…Moreover, they may see their parenting stress as personal deficiencies in isolation, rather than a problem that all parents are likely to encounter, which may hinder their development of self‐compassion. In addition, previous research has shown that parents perceived parenting stress could reduce their self‐esteem (Jeong Won & Hun‐ha, 2020) and self‐efficacy (Deater‐Deckard, 2017). Therefore, parenting stress might affect parents' self‐compassion.…”
Section: Introductionmentioning
confidence: 99%
“…Recently, with in‐depth exploration of the Theory of Dyadic Illness Management, APIM is increasingly applied to estimate inherent interdependence between dyadic ones in different situations. Cross‐sectional and longitudinal research all indicated children's emotion and parents' perception of children were connected and interacted with their physiological and psychological states (Fagan & Palkovitz, 2019; Han & Lee, 2020; Jeong & Hun‐Ha, 2020; Milan & Carlone, 2018). However, interaction of QoL and perspective of children's transition readiness concerning dyadic phenomena between parent–child relationships are rarely considered relevant.…”
Section: Introductionmentioning
confidence: 99%